Study on the age-period-cohort effects of cognitive abilities among older Chinese adults based on the cognitive reserve hypothesis - Qian Yang; Tong Yu (BMC Geriatrics)
Abstract Background Cognitive abilities serves as a critical indicator of healthy aging. As China progresses into a stage of advanced population aging, there has been a significant increase in the number of elderly individuals experiencing age-related cognitive decline. Despite this demographic shift, there is a paucity of longitudinal research examining cognitive abilities among older Chinese adults over extended time periods. This study aims to investigate changes in cognitive abilities and explore group differences among older Chinese adults aged 65 to 110 years, employing a multidimensional temporal approach that encompasses age, period, and birth cohort effects. Methods This study utilizes data from eight waves of the Chinese Longitudinal Healthy Longevity Survey (CLHLS), spanning from 1998 to 2018. The dataset comprises 94,116 observations from 36,157 unique participants. Cognitive abilities are assessed using Mini-Mental State Examination (MMSE) scores as a proxy measure. To address the issue of perfect collinearity in the temporal dimension, the study employs the Hierarchical Age-Period-Cohort Cross-Classified Random Effects Model (HAPC-CCREM). This model allows for the examination of age effects, period effects, and cohort effects on cognitive abilities among older Chinese adults. In the model specification, age is treated as a fixed effect, while period and birth cohort are incorporated as random effects. Drawing upon the cognitive reserve hypothesis, the study investigates significant factors influencing cognitive abilities in this population. Results At the fixed-effect level, demographic factors, health behaviors, self-rated health, subjective well-being, and childhood adversity significantly influence cognitive abilities among older Chinese adults. The age effects are significant, with cognitive abilities exhibiting an inverted U-shaped curve across the lifespan. At the random-effect level, period effects are significant, revealing a gradual annual increase in overall cognitive levels among older Chinese adults since 2008. Cohort effects are also significant, demonstrating an increasing trend in overall cognitive levels for the earlier-born cohorts in the first six groups. Conversely, later-born cohorts in the latter five groups show a declining trend in overall cognitive levels. Notably, period effects significantly enhance cohort effects. Conclusions The cognitive reserve hypothesis supports the significance of the majority of identified influencing factors. Cognitive abilities demonstrate an accelerating decline with increasing age, following an evolutionary trajectory consistent with physiological principles among older Chinese adults. Since 2008, cognitive abilities have shown a monotonic increasing trend annually, further validating the Flynn effect in this population. The cognitive abilities of the six earlier-born cohorts exhibit an increasing trend, supporting the compression of morbidity hypothesis. Conversely, the cognitive abilities of the five later-born cohorts show a declining trend, supporting the expansion of morbidity hypothesis. These findings collectively contribute to our understanding of cognitive aging patterns and their underlying mechanisms among older Chinese adults.